ANALISIS FAKTOR-FAKTOR YANG MEMENGARUHI PENDAPATAN PETANI PADI DI KECAMATAN PATAMPANUA KABUPATEN PINRANG - Bahruddin, Bahruddin (Economos : Jurnal Ekonomi dan Bisnis, 2020)
This study aims to analyze whether factors of land area, labor force, fertilizer, and pesticide use factors and agricultural technology have a significant effect on the income of rice farmers in Patampanua District, Pinrang Regency. The collection techniques used are observation, documentation, and interviews. The data analysis technique in this study uses multiple linear regression analysis, this analysis is used to find out the factors that influence the income of rice farmers in Patampanua District, Pinrang Regency. The results showed that based on the model summary table the value of F count = 4072,541 was obtained while using the excel formula obtained the value of Ftable = 2,312 which means Fcount> Ftable then Ho was rejected and Ha was accepted, meaning that there was a significant simultaneous effect between land area, labor, pesticide use, fertilizer, and the use of technology to farmers' income in Patampanua District, Pinrang Regency. Simultaneous correlation between the land area (X1), the number of labor (X2), use of pesticides (X3), fertilizer (X4), use of technology (X5) to farmers' income (Y) in Patampanua Subdistrict, Pinrang District obtained values of r = 0.998. This value shows a very strong positive relationship simultaneously between variables of land area, labor, use of pesticides, fertilizers, use of technology to farmers' income. Contribution or determination is given by variable land area, labor, use of pesticides, fertilizers, use of technology to farmers' incomes. is 99%. This means that the five independent variables contribute to an influence of 99% to farmers' income, 1% is influenced by other variables not included in the study.